Junior High School English Teachers’ Challenges in Teaching English at Rural Area - Siti Hardiah Nengsi; Sahraini; Magfirah Thayyib; Wisran (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate the challenges faced by English teachers in rural junior high schools and the strategies they employ to address these challenges. The research was conducted at SMPN 1 Rongkong using a qualitative case study approach. Data were collected through classroom observations and semi-structured interviews with three English teachers. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal eight major challenges, namely: curriculum implementation, inadequate school infrastructure, limited instructional time and teacher qualifications, students’ lack of vocabulary mastery, low learning motivation, limited teaching resources and internet access, geographical isolation, and lack of parental support. Among these, limited resources and low student motivation were identified as the most dominant challenges. Teachers addressed these issues through adaptive and creative strategies, such as contextualized teaching, the use of local materials, interactive activities, and collaboration with parents. This study highlights the need for greater institutional support, improved infrastructure, and targeted teacher training to enhance English language teaching in rural areas. The findings provide practical implications for policymakers, educators, and stakeholders in improving the quality of rural education in Indonesia.